SLPHT SEBAGAI LEMBAGA PEMBERDAYAAN PETANI (IPM FARMERS FIELD SCHOOL, AN AGENT OF FARMERS EMPOWERMENT) - Martono, Edhi (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2006)
Farmers empowerment through informal institution has a long history in modern Indonesian farming. Some groups evolved from farmers' own iniatitive, but many were formed after the government's urging. SLPHT (Integrated Pest Management Farmer Field School), an unconventional way to release IPM program and concept has relatively suceeded in institutionalizing farmers by dynamizing farmer groups. Although this has been an advantageous progress, the problem lies in care, management and funding for those institutized empowerment. Without careful planning in maintenance, management and funding, the success of these efforts may prove futile.Keywords: Farmers Empowerment, Institutional, Farmers Field School.